Perencanaan Strategis Pelaksanaan Tugas dan Fungsi Baru Kantor Wilayah Direktorat Jenderal Perbendaharaan Sebagai Representasi Kementerian Keuangan dan Pengelola Kebijakan Fiskal di Daerah (Studi Kasus di Kanwil DJPB Propinsi Jawa Timur) - , Viera Martina Rachmawati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of this research is to analyze the internal environment owned and external environment faced by Kanwil DJPB Propinsi Jawa Timur as well as formulate steps required in conducting strategy formulation through development of advantages owned in order to anticipate the threats that arise due to change in new job and function in Kanwil DJPB. This research uses descriptive method with qualitative analysis technique. Data collection is done though observation, interviews and documentation study. Data analysis technique in this research uses data analysis technique established by Miles and Huberman (2009) where analysis covers three streams of activities that occur simultaneously namely: 1) data reduction, 2) data presentation, and 3) drawing conclusion/verification. Data analysis process is already done while conducting interviews guided by research objective. In this study the author conducts data presentation in the form of narrative text from results of usage of internal environment analysis, external environment analysis and usage of SWOT matrix. Using data presentation methods above and the analyzed using strategic planning model by Bryson. Research results identify strategic issues in the strategic planning of implementation of new job and function in Kanwil DJPB Propinsi Jawa Timur is the human resource issue, usage issue and mastering information and communication technology, as well as requirement to optimize synergy with stakeholders. Alternative strategy that can be conducted by Kanwil DJPB Jawa Timur to handle strategic issues are to correct the internal management namely handling the weaknesses and threats that slow down the implementation of new job and function as well as utilize existing potential. Other than that, Kanwil DJPB Propinsi Jawa Timur has to develop a pattern of collaboration and communication relationship with stakeholders for the smoothness of new job and function implementation. The strategies conducted are: 1) Increase the competence and professionalism of employees in Kanwil DJPB Propinsi Jawa Timur, either in functional areas as well as the acquisition and utilization of information and communication technology to develop working methods that are responsive, responsible and accountable for the implementation of new tasks and functions to achieve maximum output, 2) Build Communication Forum development that serves as a container of synergy between the Kanwil DJPB Propinsi Jawa Timur with stakeholders related data and information for the smooth implementation of the new tasks and functions, and the opportunities for cooperation that can be done in the future.